Pregnancy-Associated Giant Abdominal Desmoid Tumor: A Case Report of Active Surveillance and Surgical Management - Song XH; Hu Y; Pan Y (International Journal of Women's Health)
Xiao Hong Song,1 Ying Hu,2 Yongmiao Pan3 1Department of Obstetrics and Gynecology, Hangzhou Women’s Hospital, Hangzhou, People’s Republic of China; 2Department of Surgery, Hangzhou Women’s Hospital (Hangzhou Maternity and Child Health Care Hospital), Hangzhou, People’s Republic of China; 3Department of Obstetrics, Women’s Hospital School of Medicine Zhejiang University, Hangzhou, People’s Republic of ChinaCorrespondence: Xiao Hong Song, Email songxh8866@163.com Yongmiao Pan, Email Panyongm@zju.edu.cnObjective: There is not much data on pregnancy-related desmoplastic fibroma (DF), and the effectiveness of active surveillance as a primary treatment strategy remains uncertain. Thus, our case illustrates that DF tumors can persist into late pregnancy. Termination of pregnancy in conjunction with surgical removal of the tumor may reduce trauma and complications, ultimately resulting in a healthy infant.Case Presentation: This case describes a pregnant woman with a suspected desmoid fibromatosis tumor who refused termination of pregnancy, opting for close monitoring until late gestation and successfully delivering a healthy baby.Conclusion: This case reveals the feasibility and potential safety of individualized, multidisciplinary management approaches - such as active surveillance followed by timely surgical intervention - for DF in pregnancy. It highlights the importance of balancing maternal and fetal risks and presents insights that may assist the clinical-decision making process in similarly complex scenarios involving pregnancy-related DF.Keywords: desmoid tumors, aggressive fibromatosis, targeted therapy, active surveillance, pregnancy